Successful ventricular tachycardia radioablation in a patient with previous chemical pleurodesis: A case report - Pavone, Chiara; Scacciavillani, Roberto; Narducci, Maria Lucia; Cellini, Francesco; Pelargonio, Gemma; Bencardino, Gianluigi; Perna, Francesco; Spera, Francesco; Pinnacchio, Gaetano; Sanna, Tommaso; Valentini, Vincenzo; Crea, Filippo (Frontiers in Cardiovascular Medicine, 2022)
Introduction Stereotactic arrhythmia radioablation (STAR) is a novel technique for the ablation of ventricular tachycardia in patients with contraindications to standard procedures, i.e., radiofrequency ablation. Case presentation We report the case of a 73-year-old man with non-ischemic dilated cardiomyopathy and recurrent VT episodes. Electroanatomic mapping showed VT prevalently of epicardial origin, but direct epicardial access through subxyphoid puncture could not be performed due to pleuropericardial adhesions from a past history of chemical pleurodesis. STAR was performed, with no VT recurrence at 6 months follow-up. Conclusions Previous experiences with STAR have demonstrated its importance in the management of patients with refractory VT in whom other ablation strategies were not successful. Our case report highlights the use of STAR as a second choice in a patient with an unfavorable VT anatomical location and technical limitations to an optimal radiofrequency ablation. Moreover, it confirms STAR's effectiveness in the ablation of complex transmural lesions, which are more often associated with non-ischemic structural heart disease.